Methanogen Productivity and Microbial Community Composition Varies With Iron Oxide Mineralogy - Gadol, Hayley J.; Elsherbini, Joseph; Kocar, Benjamin D. (Frontiers in Microbiology, 2022)
Quantifying the flux of methane from terrestrial environments remains challenging, owing to considerable spatial and temporal variability in emissions. Amongst a myriad of factors, variation in the composition of electron acceptors, including metal (oxyhydr)oxides, may impart controls on methane emission. The purpose of this research is to understand how iron (oxyhydr)oxide minerals with varied physicochemical properties influence microbial methane production and subsequent microbial community development. Incubation experiments, using lake sediment as an inoculum and acetate as a carbon source, were used to understand the influence of one poorly crystalline iron oxide mineral, ferrihydrite, and two well-crystalline minerals, hematite and goethite, on methane production. Iron speciation, headspace methane, and 16S-rRNA sequencing microbial community data were measured over time. Substantial iron reduction only occurred in the presence of and the presence of hematite and goethite had little effect on methane production throughout the incubations. In ferrihydrite experiments however, the time taken to reach the maximum methane production rate was slower than under other conditions, but methane production, eventually occurred in the presence of ferrihydrite. This is likely We suggest that this is due to ferrihydrite transformation into more stable minerals like magnetite and goethite or surface passivation by Fe(II). While all experimental conditions enriched for Methanosarcina, only the presence of ferrihydrite enriched for iron reducing bacteria Geobacter. Additionally, the presence of ferrihydrite continued to influence microbial community development after the onset of methanogenesis, with the dissimilarity between communities growing in ferrihydrite compared to no-Fe-added controls increasing over time. This work improves our understanding of how the presence of different iron oxides influences microbial community composition and methane production in soils and sediments.